Рецепція особистості Михайла Щепкіна у лінгвосвідомості Тараса Шевченка (на матеріалі "Щоденника") - Сирко, І. (Культура слова, 2019)
У статті досліджено специфіку рецепції особистості Михайла Щепкіна у лінгвосвідомості Тараса Шевченка. Продемонстровано, що основу антропонімікону творів Т. Шевченка, зокрема «Щоденника», становлять імена сучасників письменника, які відігравали важливу роль у його житті. Семантично-оцінні парадигми цих власних назв репрезентовані крізь призму індивідуального сприймання й індивідуального світогляду Т. Шевченка, вони переконливо виявляють його ставлення до згадуваних осіб у конкретних життєвих, побутових, комунікативних ситуаціях. Акцентовано домінування позитивних оцінок постаті М. Щепкіна, що оприявнюють його рецепцію як щирої людини, талановитого актора, близького друга. Актуальні для таких контекстів змістотвірні архісеми ‘людяність’, ‘порядність’, ‘талановитість’, ‘товариськість’ визначають позитивну оцінність контекстів, у яких згадано ім’я Михайла Щепкіна, і формують загальне емотивне значення однойменного антропонімного концепту. The article deals with the peculiarities of the Mykhailo Shchepkin`s figure reception in linguistic consciousness of Taras Shevchenko. It has been demonstrated that the basis of the literary-and-artistic anthroponymicon of T. Shevchenko`s works, including the anthroponymicon of his “Diary”, are the names of his contemporaries, who played an important role in his life – M. Shchepkin, Y. Lazarevsky, P. Kulish, O. Bodiansky, M. Maximovich, etc. The semantic-and-evaluative paradigms of these proper names are represented through the prism of T. Shevchenko’s individual perception and outlook. They convincingly show his attitude to the mentioned persons in different specific everyday, communicative situations. We have emphasized the dominance of positive appraisals of M. Shchepkin’s figure, which reveal the reception of him as a unique and sincere person (amazing old man, sincere Mikhail Semenovich, kindest creature), a talented actor (great man, great artist, brilliant actor, best comedian, unique comedian, irresistible Shchepkin, artist-veteran, patriarch-artist), a close friend (great friend, my only friend, my sincere, my unforgettable, nobler friend, kind friend, sincere friend). Topical for such contexts lexemes ‘uniqueness’, ‘ humaneness’, ‘honesty’, ‘talent’ and ‘sociability’ determine the positive evaluation of most contexts in which the name of Mykhailo Shchepkin is mentioned. They form the overall emotional meaning of the concept of the same name. Means of intimization of the image of M. Shchepkin – friend have been noted, in particular due to the combination of the anthroponym with the possessive pronoun mine.